Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the system of linear equations:
[tex]\[ \begin{cases} 3x + 7y = 1 \\ y = x - 7 \end{cases} \][/tex]
we'll use the substitution method given that the second equation is already solved for [tex]\( y \)[/tex]:
1. Substitute [tex]\( y = x - 7 \)[/tex] into the first equation [tex]\( 3x + 7y = 1 \)[/tex]:
[tex]\[ 3x + 7(x - 7) = 1 \][/tex]
2. Simplify the equation to solve for [tex]\( x \)[/tex]:
[tex]\[ 3x + 7x - 49 = 1 \][/tex]
Combine like terms:
[tex]\[ 10x - 49 = 1 \][/tex]
Add 49 to both sides:
[tex]\[ 10x = 50 \][/tex]
Divide both sides by 10:
[tex]\[ x = 5 \][/tex]
3. Substitute [tex]\( x = 5 \)[/tex] back into the second equation [tex]\( y = x - 7 \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 5 - 7 \][/tex]
[tex]\[ y = -2 \][/tex]
So, the solution to the system of equations is [tex]\( (5, -2) \)[/tex].
4. Verify which option matches this solution:
[tex]\[ \begin{array}{l} A: (2, -5) \\ B: (5, -2) \\ C: (4, -3) \\ D: (3, -4) \end{array} \][/tex]
The correct answer is [tex]\( (5, -2) \)[/tex], which corresponds to.
[tex]\[ \boxed{B} \][/tex]
[tex]\[ \begin{cases} 3x + 7y = 1 \\ y = x - 7 \end{cases} \][/tex]
we'll use the substitution method given that the second equation is already solved for [tex]\( y \)[/tex]:
1. Substitute [tex]\( y = x - 7 \)[/tex] into the first equation [tex]\( 3x + 7y = 1 \)[/tex]:
[tex]\[ 3x + 7(x - 7) = 1 \][/tex]
2. Simplify the equation to solve for [tex]\( x \)[/tex]:
[tex]\[ 3x + 7x - 49 = 1 \][/tex]
Combine like terms:
[tex]\[ 10x - 49 = 1 \][/tex]
Add 49 to both sides:
[tex]\[ 10x = 50 \][/tex]
Divide both sides by 10:
[tex]\[ x = 5 \][/tex]
3. Substitute [tex]\( x = 5 \)[/tex] back into the second equation [tex]\( y = x - 7 \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 5 - 7 \][/tex]
[tex]\[ y = -2 \][/tex]
So, the solution to the system of equations is [tex]\( (5, -2) \)[/tex].
4. Verify which option matches this solution:
[tex]\[ \begin{array}{l} A: (2, -5) \\ B: (5, -2) \\ C: (4, -3) \\ D: (3, -4) \end{array} \][/tex]
The correct answer is [tex]\( (5, -2) \)[/tex], which corresponds to.
[tex]\[ \boxed{B} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.